Inserção de lógica de programação no ensino básico usando linguagem PYTHON e Biblioteca PYGAME - Roque, Matheus Maia (2017)
This project aims to open questions about the methodologies used to teach programming language and logic for basic education students and the failure/lack of this practice, resulting in professionals and graduated students with problems to develop this ability. The justification can be effected by the bibliographic study done by articles which talk about development of projects aimed the insertion of programming in basic education, as well as the realization of a search with students from different universities. This search tries to show the difficult to develop programming and logic ability in graduating students. This project brings a case study using programming language Python and the theme Arcade Games, it was applied in the Seara da Ciência of the Federal University of Ceará (UFC). It was chosen high school students from Fortaleza/CE - Brazil to participate of this project. The case study goals are the development of a methodology teaching in programming logic and the evaluation of the effectiveness in the learning process in the students. It was proven that this project had a high satisfactory among the participating students, and the Python language together with the Pygame Library could bring the interest of the student in learn programming logic and awaking the creativity to solve different problems. This project had result in a elaboration of a didactic handout that can be used in future projects.